In-silico approaches to unravel the efficacy of naturally occurring C–C and C–O–C type biflavonoids towards the inhibition of MDM2–p53 interactions - Suvankar Karmakar; Animesh Sen; Sourav Majumdar; Bula Singh; Anup Pramanik; Samiran Mondal (Discover Chemistry)
Abstract The p53 protein is essential for controlling the cell cycle and promoting apoptosis, which are critical processes in preventing tumor development. MDM2 acts as a negative regulator of p53 by facilitating its degradation, thereby diminishing its ability to suppress tumors. In the present study, a total of six naturally occurring biflavonoids, categorized into C–C type (amentoflavone, robustaflavone, and agathisflavone) and C–O–C type (ochnaflavone, hinokiflavone, and delicaflavone) were investigated, as potential therapeutic agents to enhance p53 activity and mitigate MDM2’s suppressive effects. Using molecular docking and molecular dynamics simulations, the study assessed the ability of these biflavonoids to inhibit the p53–MDM2 interaction. Both types of biflavonoids demonstrated potential in obstructing the p53-binding domain of MDM2. Among them, amentoflavone, a C–C type biflavonoid, showed the most pronounced inhibitory effect, with a higher binding affinity than the reference compound nutlin-3. This suggests that amentoflavone and similar compounds could serve as promising lead candidates for developing new anticancer therapies targeting the p53–MDM2 interaction.